In vitro ANALYSIS OF BIOFILM FORMATION AND ANTIBIOTIC RESISTANCE OF UROPATHOGENIC Escherichia coli (Applied Biological Research, 2024)
Urinary tract infections are an exceedingly common worldwide problem, caused  mostly by Gram-negative bacteria, especially Escherichia coli. Microbial  biofilms are considered a serious public health problem. The potential of  uropathogenic E. coli (UPEC) to produce biofilm was explored in the present  study. The Congo red agar, tube- and tissue culture plate methods were used to  evaluate the formation of biofilm by E. coli isolates. Of the 155 isolates, 101, 106  and 90 isolates were positive for these three methods, respectively. Subsequently,  the sensitivity of E. coli isolates to antimicrobial agents (amikacin, cefepime,  cefixime, cefotaxime, cefpodoxime, ceftazidime, ceftriaxone, ciprofloxacin,  nitrofurantoin, gentamycin, nalidixic acid, ofloxacin and pefloxacin) was tested.  There was no difference in the rate of biofilm detection between Congo red agar  method and tube method. The antibiotic sensitivity test revealed that the biofilm producing isolates were multi-drug resistant. The study emphasized the  necessity for developing alternative therapeutic approaches to overcome multi drug resistance arising from biofilm formation of UPEC.
Keywords: Antibiotic resistance; biofilm; uropathogenic Escherichia coli; urinary tract infection